Genomic Evolution and Personalized Therapy of an Infantile Fibrosarcoma Harboring an NTRK Oncogenic Fusion. (25th May 2022) - Thorwarth, Anne; Haase, Kerstin; Röefzaad, Claudia; Pajtler, Kristian W.; Schramm, Kathrin; Hauptmann, Kathrin; Behnke, Anke; Vokuhl, Christian; Elgeti, Thomas; Gratopp, Alexander; Schulte, Johannes H.; Scheer, Monika; et al.
Abstract :